Evaluation of the Use of Electronic Medical Records in Improving the Quality of Outpatient Services at the KarangPloso Health Center - Annastasia, Shinta; Rusdian Ikawati, Fita (Universitas Ibn Khaldun Bogor, 2025)
The use of electronic medical records (RME) provides various benefits, such as reducing medical errors, improving the quality of insurance claim documents, and lowering the operational costs of health centers. This study aims to evaluate the success of the use of RME in outpatient care in terms of content completeness and identify the challenges faced. The research method used is qualitative research, Qualitative research is research that originates from an inductive mindset. This study raises the topic of evaluating the use of outpatient RME using 5M management elements (Man, Money, Material, Machine, Method). By using the head of medical records as a key informant and conducting in-depth interviews with 6 health center officers. The results of the research are to find problems and improvement efforts so that the quality of service can be maintained. Conclusion The outpatient RME that is currently being carried out is running well and the officers have been able to understand and implement the RME optimally, however, there are still obstacles related to the access rights owned by each officer but the authority owned by each officer is the same because they can access all menus.